Wide geographical dissemination of the multiresistant Staphylococcus capitis NRCS-A clone in neonatal intensive-care units. (January 2016) - Butin, M.; Rasigade, J.-P.; Martins-Simões, P.; Meugnier, H.; Lemriss, H.; Goering, R.V.; Kearns, A.; Deighton, M.A.; Denis, O.; Ibrahimi, A.; Claris, O.; Vandenesch, F.; et al.
Abstract: Nosocomial late-onset sepsis represents a frequent cause of morbidity and mortality in preterm neonates. The Staphylococcus capitis clone NRCS-A has been previously described as an emerging cause of nosocomial bacteraemia in French neonatal intensive-care units (NICUs). In this study, we aimed to explore the possible unrecognized dissemination of this clone on a larger geographical scale. One hundred methicillin-resistant S. capitis strains isolated from neonates ( n  = 86) and adult patients ( n  = 14) between 2000 and 2013 in four different countries (France, Belgium, the UK, and Australia) were analysed with Sma I pulsed-field gel electrophoresis (PFGE) and dru typing. The vast majority of NICU strains showed the NRCS-A pulsotype and the dt11c type (96%). We then randomly selected 14 isolates (from neonates, n  = 12, three per country; from adult patients, n  = 2), considered to be a subset of representative isolates, and performed further molecular typing ( Sac II PFGE, SCC mec typing, and multilocus sequence typing-like analysis), confirming the clonality of the S. capitis strains isolated from neonates, despite their distant geographical origin. Whole genome single-nucleotide polymorphism-based phylogenetic analysis of five NICU isolates (from the different countries) attested to high genetic relatedness within the NRCS-A clone. Finally, all of the NRCS-A strains showed multidrug resistance (e.g. methicillin and aminoglycoside resistance, and decreased vancomycin susceptibility), with potential therapeutic implications for infected neonates. In conclusion, this study represents the first report of clonal dissemination of methicillin-resistant coagulase-negative Staphylococcus clone on a large geographical scale. Questions remain regarding the origin and means of international spread, and the reasons for this clone's apparent predilection for neonates.